Flowering time and its relationship to vegetative development in maize (Zea mays L.) - Passas, Hildrun Jutta (The University of Edinburgh, 1994)
All organisms go through distinct phases of development during ontogenesis. In plants, shoot development has traditionally been divided into two phases of development distinguished by the the ability to flower. The non-flowering, juvenile phase of development is followed by the adult phase of development, during which flowering can occur. Frequently observed modifications in the vegetative morphology of the shoot are thought to reflect the transition to a phase in which the shoot is competent to flower, yet conclusive evidence for this assumption is lacking. An alternative model proposed here may provide a better framework for the genetic analysis of shoot development. In this model, shoot development is partitioned into three phases: the early vegetative and late vegetative phases of development, which are defined by phase-specific vegetative traits, and a reproductive phase of development. These phases are expressed in a spatial sequence as a result of the polar nature of shoot growth. In maize, the early vegetative phase is marked by traits such as the presence of a visible form of epicuticular leaf wax and round epidermal leaf cells in cross section. In the late vegetative phase, the visible leaf wax is absent, the epidermal cells are more rectangular in cross section and trichomes are expressed on the leaf blades. The reproductive phase of development is characterised first by a brief, photoperiod sensitive period and later by the differentiation of inflorescences. The aim of this study is to investigate whether this three-phase model provides an adequate conceptual framework. To this end, the relationship between the transition from early vegetative to late vegetative growth and flowering in maize is studied using a genetic approach.

Results show that the early flowering trait does not alter the rate of leaf initiation. Rather, the overall length of the vegetative development is reduced in early flowering plants, resulting in the production of fewer leaves. This reduction in leaf number affects the vegetative phases of development in different ways; either only the late vegetative phase of development is reduced or the early vegetative and the late vegetative phases are both shortened, as determined by phase-specific traits. This difference is dependent on the inbred background and not on the early flowering trait, as determined by genetic, molecular, and physiological techniques. Therefore, in one species, but in different inbred backgrounds, vegetative phase change and reproductive maturity can be independent or regulated coordinately, indicating that a three-phase model of shoot development is an adequate conceptual framework. Finally, the early flowering trait is placed in a pathway regulating the reproductive phase of development. In the late flowering genotypes examined, a longer vegetative phase is reflected only in a longer late vegetative phase. The expression of the early vegetative phase is unaffected. A working model of shoot development in maize is proposed.